Epidemiology of Depression, Anxiety and Stress Symptoms in Veterans' Wives - S.M. Seyyed Talebi; A. Rafieepour (Afarand Scholarly Publishing Institute, 2017)
Aims: The major complications of any war are physical and mental problems for those directly involved in it. Many studies have shown that taking care of these veterans also greatly affects the health and quality of life of their spouses. The aim of this study was to study the epidemiology of symptoms and emotional syndrome of depression, anxiety and tension disorders in over 25% male veterans' wives and to investigate the role of demographic factors as predictors of these disorders. Instrument & Methods: In this descriptive survey in 2009, 377 wives of over 25% veterans of Tehran City, Iran, who were referred to the psychiatric services centers of Tehran Martyr Foundation and Veterans Affairs were selected by randomized cluster sampling method. The research instrument was Depression, Anxiety and Stress Questionnaire (DASS-21). Data was analyzed with SPSS 21 software using independent T, one-way variance analysis and Scheffechr('39')s post hoc tests. Findings: 76% of the cases had emotional symptoms of the disorders from a weak to very severe stages. The difference between mean scores of veteranschr('39') spouses was significant in terms of age group, physical health, recreational activities and residential ownership in all three subscales, based on the educational status variable and the number of children in the subscales of anxiety and in terms of employment status variable in the subscales of depression and anxiety (p<0.05). Conclusion: 76% of over 25% veterans' wives of Tehran City, Iran, have certain symptoms and emotional symptoms of depression, anxiety and tension disorders. Also, demographic characteristics affect the level of depression, anxiety and tension in veterans' wives.